Serum adropin level and ENHO gene expression in systemic sclerosis - Yolbas, Servet; Kara, Murat; Yilmaz, Musa; Aydin, Suleyman; Koca, Suleyman Serdar (Springer London Ltd, 2016)
Adropin, a secreted protein, is encoded by the energy homeostasis associated (ENHO) gene. It has been implicated in the several physiological and pathological processes such as angiogenesis and apoptosis. Therefore, the aim of present study was to investigate serum adropin levels and ENHO gene expressions in systemic sclerosis (SSc) characterized by vasculopathy, inflammation, and progressive fibrosis of the skin and internal organs. The study includes 27 patients with SSc, 39 patients with Beh double dagger et's disease (BD), and 20 healthy controls (HC). Serum adropin levels and ENHO gene expressions by peripheral blood mononuclear cells were analyzed by ELISA method and by real-time PCR, respectively. The serum adropin levels were higher in the SSc and BD groups than in the HC group (p = 0.023 and p < 0.001, respectively). However, there were no significant differences among the groups in terms of ENHO gene expressions (p (ANOVA) = 0.149). There was no significant difference between the limited and diffuse cutaneous subtypes of SSc in terms of serum adropin level and ENHO gene expression. Moreover, serum adropin level and ENHO gene expression were not associated with the disease activity and severity indexes. ENHO gene expression was correlated with the triglyceride levels in the BD group (r = -0.426, p = 0.027). The augmented serum adropin levels may be expected in the chronic inflammatory disease and seem not to be characteristic of only SSc. However, further studies are needed to explain the precise role of adropin in SSc.
Annual Meeting of Spondyloarthritis-Research-and-Treatment-Network (SPARTAN) -- JUL 25-26, 2015 -- Denver, CO
Keywords: Adropin; Behcet's disease; ENHO; Systemic sclerosis